TINGKAT DAYA LAYAN PRASARANA BERDASARKAN PERKEMBANGAN WILAYAH DI KABUPATEN PASAMAN TAHUN 2006-2016 - Melda Latifah Hanum; Fitriana Syahar (JURNAL BUANA, 2020)
This study aims to measure variations in the level of availability of facilities and infrastructure as well as service capacity of facilities and infrastructure based on regional development in Pasaman Regency in 2006-2016. The population in this study were all districts in Pasaman Regency. This population as well as a sample. The data used are secondary data obtained from several agencies such as the Central Statistics Agency and the Pasaman Regency Public Works Agency. Data collection techniques used are documentary study techniques. To measure the level of availability of facilities and infrastructure and the level of service capacity of facilities and infrastructure using a weighted scalogram analysis. Based on the results of the study, it is known that 1) spatial variations in the level of availability of facilities and infrastructure in Pasaman Regency in 2006-2016 included in the high classification are in Lubuk Sikaping and Dua Koto Districts. 2) the variation in spatial level of service capacity of facilities and infrastructure in Pasaman Regency in 2006-2016 has changed. In 2006, included in the high classification were in Simpang Alahan Mati Subdistrict, Lubuk Sikaping Subdistrict, Padang Gelugur Subdistrict, and Mapat Tunggul Subdistrict. While in 2016 included in the high classification are in Simpang Alahan Mati District, Padang Gelugur District, Mapat Tunggul District, and Mapat Tunggul Selatan District.